Cannon-fever: Beethoven, Waterloo and the Noise of War. Issue 3 (October 2018) - Shaw, Philip
Abstract : Originally written to commemorate the Duke of Wellington's victory over Joseph Bonaparte at the Battle of Vitoria in Spain on 21 June 1813, Wellington's Victory, or, the Battle of Vitoria ( Wellington's Sieg oder die Schlacht bei Vittoria ), Op. 91 became, in the months following the Battle of Waterloo, 'a national stock-piece' ( Literary Gazette, 1817, 91). Based around a simple, not to say simplistic, opposition between French and English musical motifs – 'Rule Britannia' and 'God Save the King' for the British, and ' Marlborough s'en va-t-en guerre ' (a tune better known in English as 'For He's a Jolly Good Fellow') – the symphony moves towards a carefully notated clash of arms, involving rapid bursts of musketry and cannon fire from opposing orchestral 'sides', and rhythmic simulations of galloping cavalry. However, as contemporary accounts of performances of the symphony reveal, the excessive frequency of the loud cracks, bangs and crashes, often deployed by live artillery, made for uncomfortable listening, evoking Goethe's description of the disorientating effects of 'cannon-fever' ( kanonenfieber ). In its activation of the 'noise' of war, a mimetic dissonance at odds with the formal unities of the heroic style, Beethoven's symphony thus subverts its assumed status as a pièce d'occasion while also emphasising the sense in which the sounds of battle exceed the regulatory parameters of the Kantian sublime. This article argues that although the Wellington symphony was denounced by critics as a 'minor' piece, it highlights an emergent note of discontent in Beethoven's music with the appropriation of music for triumphalist ends.